Dual stimulus-triggered bioorthogonal nanosystem for spatiotemporally controlled prodrug activation and near-infrared fluorescence imaging. Issue 26 (14th March 2023) - Zhao, Zhongyi; Zong, Qingyu; Li, Jun; Jiang, Maolin; Wang, Kewei; Yuan, Youyong
Abstract : Herein, we developed a dual stimulus-triggered bioorthogonal nanosystem that combines low pH and cathepsin B-triggered delivery carriers with a bioorthogonal reaction-activated prodrug and fluorescent probe to enhance tumor therapy and imaging. Abstract : In this study, we combined low pH and cathepsin B dual-stimulus-triggered delivery carriers with a bioorthogonal reaction-activated prodrug to achieve regulated activation of the prodrug. A workable method for precise tumor therapy and imaging is provided by the bioorthogonal reaction, which activates the prodrug and fluorescent probe.